The Kuwait National Primary Immunodeficiency Registry 2004–2018 - Al-Herz, Waleed; Al-Ahmad, Mona; Al-Khabaz, Ahmad; Husain, Ahmed; Sadek, Ali; Othman, Yasmeen (Frontiers in Immunology, 2019)
Objective: To present the report from the Kuwait National Primary Immunodeficiency Registry between 2004 and 2018. Methods: The patients were followed prospectively between January 2004 and December 2018 and their collected data included sociodemographic, diagnosis, clinical presentation, laboratory tests and treatment. Results: A total of 314 PID patients (165 males and 149 females) were registered during the study period. Most of the patients (n=287, 91.4%) were Kuwaiti nationals and the prevalence among Kuwaitis was 20.27/100,000 with a cumulative incidence of 24.96/100,000 Kuwaitis. The distribution of the patients according to PID categories was as follow: immunodeficiencies affecting cellular and humoral immunity, 100 patients (31.8%); combined immunodeficiencies with associated syndromic features, 68 patients (21.7%); predominantly antibody deficiencies, 56 patients (17.8%); diseases of immune dysregulation, 47 patients (15%); congenital defects of phagocyte number or function, 20 patients (6.4%); autoinflammatory disorders, 1 patient (0.3%); and complement deficiencies, 22 patients (7%). The mean age of the patients at onset of symptoms was 26 months while the mean age at diagnosis was 53 months and the mean delay in diagnosis was 27 months. Most of the patients (n= 272, 86%) had onset of symptoms before the age of 5 years. Parental consanguinity rate within the registered patients was 78% and a positive family history of PID was noticed in 50% of the patients. Genetic testing was performed in 69% of the patients with an overall diagnostic yield of 90%. Mutations were identified in 46 different genes and more than 90% of the reported genetic defects were transmitted by an autosomal recessive pattern. Intravenous immunoglobulins and stem cell transplantation were used in 58% and 25% of the patients, respectively. There were 81 deaths (26%) among the registered patients with a mean age of death of 25 months. Conclusions: PID are not infrequent in Kuwait and the reported prevalence is the highest in the literature with increased proportion of more severe forms. Collaborative efforts including introduction of newborn screening should be implemented to diagnose such cases earlier and improve the quality of life and prevent premature deaths.